Killing Kaplanism: Flawed methodologies, the standard of proof and modernity. (July 2019) - Cullerne Bown, William
Attempts to establish a quantitative framework for policy-making in the criminal justice system in recent decades have coalesced around the problem of the standard of proof and Kaplan's influential 1968 paper. The central thread of work continues to use an equation he put forward while abandoning some of his foundational assumptions, an approach I call 'Kaplanism'. Despite a growing awareness of deficiencies, elements of this school of thought, such as the parsing of concerns into the two categories of 'error reduction' and 'error distribution', have entered the general jurisprudential discourse. Here I launch a methodological attack and claim to kill this approach. This allows me to refute Laudan and other 'consequentialist' approaches to the standard identified by Walen, Walen's own approach and an important part of Stein's underpinnings. The same tools allow me to also refute Laudan's earlier m/n meta-epistemology, Lippke's 'adage', Stewart's formalisation of Dworkin, Dahlman's Bayesian work and (at least in criminal law) Kaplow's law and economics approach. I also refute Hamer's 'conventional rationale' for the current standard, Lillquist's approach to the same and what Epps reports as 'the Blackstone principle'. The law is left with no epistemic basis for policies, which, I argue, leaves it struggling for public trust in the modern era.